Institution-induced productivity differences and patterns of international capital flows - Kiminori Matsuyama (Institute for Advanced Studies (IHS), 2013)
This paper studies theoretically how the cross-country differences in the institutional quality (IQ) of the domestic credit markets shape the patterns of international capital flows when such IQ differences cause productivity differences across countries. IQ affects productivity by changing productivity-agency cost trade-offs across heterogeneous investment projects, which have opposite effects on the investment and capital flows from exogenous productivity differences. The overall effect of IQ could generate U-shaped responses of the investment and capital flows. This means that capital could flow from middle-income to low-income and high-income countries; and starting from a low IQ, a country could experience both growth and a current account surplus after an institutional reform. More generally, the results here offer some cautions when interpreting the evidence on the role of productivity and institutional differences on capital flows and question the validity of using financial frictions as a proxy for the quality of financial institutions.
Keywords: E22; F49; O16; 330; Credit composition; domestic financial frictions; endogenous productivity; institutional quality; intertemporal trade; pledgeability; productivity-agency cost trade-off; reverse capital flows; Ushaped patterns